Factors influencing zakat on saving among muslim youth in Malaysia / Nur Fatin Syahira Nazrin - Nazrin, Nur Fatin Syahira (Faculty of Business Management, 2018)
Zakat on wealth can be further divided into zakat on employment income, gold and silver, agriculture, shares, business, savings, crops and natural sources. Zakat on saving should be paid when saving, fixed deposit, current account or unit trust funds fulfilled the nisab and haul requirement during the year. The purpose of this study is to identify the factors influencing the zakat compliance on saving among Muslim youth in Malaysia. 130 questionnaire was distributed to Muslims youth in Malaysia. The question is focus on the independent variables which consist of religiosity, knowledge, altruism and self-satisfaction. IBM SPSS Statistics V22.0 is used to analyse the relationship between the independent and dependent variables by using Frequency Analysis, Descriptive Analysis, Multiple Regression, Correlation Analysis, and Reliability Analysis. With this study we found that there is significant relationship between self-satisfaction and zakat compliance on saving among Muslim Youth in Malaysia while religion, altruism and knowledge shows there is no significant relationship towards zakat compliance on saving among Muslim Youth in Malaysia.